Higher rating of perceived exertion and lower perceived recovery following a graded exercise test during menses compared to non-bleeding days in untrained females - Delp, Morgan; Chesbro, Grant A.; Pribble, Brian A.; Miller, Ryan M.; Pereira, Hugo M.; Black, Christopher D.; Larson, Rebecca D. (Frontiers in Physiology, 2024)
The underrepresentation of the female population in exercise sciences could be attributed, at least in part, to difficulty in appropriately accounting for the effects of the menstrual cycle (MC). Previous studies examining the effects of the MC on aerobic performance and subjective measures of aerobic performance show conflicting results. Purpose: The study examined how the MC affects the objective and subjective measures of aerobic performance within untrained female participants and in comparison with untrained male participants assessed at similar time intervals. Methods: Twenty-one participants (12 females and 9 males) completed a graded exercise test (GXT) on a cycle ergometer. The female participants were tested during their early follicular (EF; menses), ovulatory (O), and mid-luteal (ML) phases of the MC. The male participants were included as the control group and were randomly assigned to a menstrual cycle phase for each visit. During GXT, maximal oxygen consumption (VO2max), respiratory exchange ratio (RER), maximal heart rate (HRmax), peak blood lactate, and rating of perceived exertion (RPE) were determined. Twenty-four hours post-exercise, the perceived recovery status (PRS) was assessed. The MC phase was estimated using basal body temperature (BBT) in the female participants. Results: The male participants obtained a higher peak power and VO2max compared to the female participants (p < 0.05). All objective measures of aerobic performance did not significantly differ across the MC phases or time points that were tested. In the untrained female participants, an effect of the MC phase on RPE was found, with RPE being higher at EF (8.92 ± 0.79) compared to O (7.67 ± 1.23; p < 0.05) and ML (7.75 ± 1.06; p < 0.05). In addition, an effect of the MC phase on PRS was found, with perceived recovery being lower at EF (6.83 ± 0.94) compared to O (8.83 ± 1.12) and ML (8.67 ± 0.65; all p < 0.005) for the untrained female participants. No significant differences in RPE and PRS were found between tests in the untrained male participants. The female participants had lower perceived recovery following EF (6.83 ± 0.94) compared with the male participants (9.00 ± 1.00; p < 0.001). Conclusion: The untrained female participants perceived greater exertion during GXT and impaired recovery following GXT in EF compared to O and ML. These results may be attributed to either a drop in female sex hormone concentrations or discomfort associated with menses. The male participants did not exhibit any changes over time. Future studies using subjective parameters such as perceived exertion to track the internal load of training in the naturally menstruating female population should consider menses.